Corporate Governance and Banking Performance amid Covid-19 in Indonesia - Asih Dwi Meilani; Zulaikha Zulaikha; Rahma Prafinta Sari (Universitas Negeri Semarang, 2022)
Purpose : This study aims to analyze the effect of good corporate governance on the performance of banking companies listed on the Indonesian Stock Exchange during Covid-19. Method : This study used a purposive sampling method as a sample selection method. A final sample from banking companies listed on the Indonesia Stock Exchange in 2020-2021 was 38. We used Multiple linear regression to analyze data. The dependent variable of this research is Return on Assets (ROA) and Return on Equity (ROE), and the Board of Commissioners, Board of Directors, audit committee, and managerial ownership as independent variables. Findings : The results of the research analysis prove that the variables of the Board of Commissioners, Board of Directors, audit committee, and managerial ownership have no significant effect on ROA. Then, the audit committee significantly and positively affects ROE; meanwhile, the Board of Commissioners, Board of directors, and managerial ownership have no significant effect. This finding implies that just the audit committee affects the ROE. Novelty : This research differs from previous studies because it focuses on the effect of GCG on banking performance during the covid-19 outbreak in Indonesia. Keywords : Good Corporate Governance, Banking Company Performance, Covid-19